Detection of recombinant type of human adenovirus C composed of type 89 and type 5 in Aichi Prefecture, Japan, 2016-2019 - Hirose, Emi; Minagawa, Hiroko; Adachi, Hirokazu; Suzuki, Masakazu; Nakamura, Noriko; Saito, Noriko; Ito, Miyabi; Mitsuoka, Chikako; Sato, Katsuhiko; Yasui, Yoshihiro (Japanese Journal of Infectious Diseases, 2025)
Recombinant human adenoviruses (HAdVs) have been reported from many countries, including Japan. We report a recombinant HAdV-C type detected in feces with gastroenteritis infection or throat swabs with upper respiratory tract inflammation of six children in Aichi Prefecture. This type may have been prevalent in the area. Between April 2014 and March 2019, we attempted to detect HAdVs in 9,483 specimens (fecal, throat swab, urine, and conjunctival swab) collected from patients with suspected viral infection. A total of 220 HAdV-C isolates were obtained and serotyped by neutralization test (NT). Of these, 62 HAdV-C strains (HAdV-C1: 15, -C2: 19, -C5: 22, -C6: 6) were genotyped by sequencing for the three regions, penton base, hexon, and fiber regions, respectively. All 62 strains were grouped into the same genotype as serotype for the hexon and fiber region. In contrast, phylogenetic analysis showed 6 of the 22 strains with serotype HAdV-C5 were grouped into HAdV-C89 for the penton base region. This type was detected as a recombinant HAdV causing SARI in China between 2017 and 2021, was found to have been persistently detected in transnational Aichi Prefecture over the same period.